POTENTIAL RISK OF LOSSES IN MAIZE CAUSED BY Dichelops melacanthus (DALLAS) (HEMIPTERA: PENTATOMIDAE) IN BRAZIL - CRUZ, IVAN; BIANCO, RODOLFO; REDOAN, ANA CAROLINA MACIEL (International Journal of Maize & Sorghum, 2016)
ABSTRACT: The incidence of the green belly stink bug, Dichelops melacanthus (Dallas) (Heteroptera: Pentatomidae), on maize crop in Brazil has increased with time, especially due to the continuous availability of food throughout theyear. This insect causes injury to seedlings, killing them shortly after their emergence from the soil. If the plant survives,it is possible to see areas with necrotic lesion that increase in a transverse pattern on the sheet, with perforations on the leaves or tillers (side shoots). This pest is currently one of the most important to maize, in conventional and Bt hybrids. The research compared the behavior of theses cultivars infested by the green belly stink bug, D. melacanthus. Bt and conventional maize cultivars were evaluated in a protected environment (greenhouse) and only Bt maize was evaluated at field. Evaluations based on plant development and insect injury occurred after seven days of the infestation period. The results indicated variability among cultivars related to insect infestation, measured by a visual scale for damage determination and plant development. Grain yield obtained from infested plots was 6352.2 kg ha-1 whereas in the noninfested plots was 8048.05 kg ha-1, equivalent to an average reduction of 21.07%. Keywords: Plant damage, grain losses, green belly stink bug. RISCO POTENCIAL DE PERDAS CAUSADAS POR Dichelops melacanthus (DALLAS)(HEMIPTERA: PENTATOMIDAE) EM MILHO NO BRASIL RESUMO - A incidência do percevejo barriga verde Dichelops melacanthus (Dallas) (Heteroptera: Pentatomidae) em milho no Brasil tem aumentado nos últimos anos, especialmente devido à disponibilidade de alimento o ano todo. A injuria provocada pelo inseto pode causar a morte da plântula reduzindo o número ideal de plantas na colheita. Se a planta sobrevive, é possível visualizar áreas necrosadas ou perfilhamento. A praga é atualmente uma das mais importantes do milho, tanto em cultivares convencionais como em cultivares Bt. A presente pesquisa comparou o comportamento destas cultivares em ambiente protegido (casa de vegetação) e no campo, avaliando a injuria provocada pela praga, o desenvolvimento da planta e a produtividade de grãos (campo). Os resultados indicaram variabilidade entre cultivares em relação à injuria e ao desenvolvimento da planta. O rendimento de grãos nas parcelas infestadas foi 6352,2 kgha-1 enquanto que nas parcelas sem infestação a produtividade foi 8048,05 kgha-1, o equivalente a uma redução média de 21,07%. Palavras-chave: Danos, perdas em rendimento de grãos, percevejo barriga-verde.